Effect of Planning and Budget Realization with Covid-19 As A Moderator Variable toward Budget Absorption in Resort Police Station Bangka Tengah - Harry Pranajaya; Lela Nurlaela Wati; Ira Geraldina (Journal of Governance Risk Management Compliance and Sustainability, 2024)
In response to the Covid-19 pandemic, the government prioritized allocating a significant portion of its resources toward preventing the spread of Covid-19. Undoubtedly, this will inevitably affect the meticulously devised programs aimed at achieving budgetary recuperation. This study aims to determine the extent to which Covid-19 affects the budget absorption of the Resort Police Station Work Unit in Bangka Tengah. This study utilizes a quantitative methodology, utilizing moderating regression analysis (MRA) for data analysis. The financial statements cover a period of 72 months, spanning from 2017 to 2022. The study discovered that both the planning and implementation of activities, as well as the regulation of the Covid-19 pandemic’s impact on planning and implementation, had a noteworthy influence on the utilization of funds at the Resort Police Station Bangka Tengah. This study demonstrates that the planning process at the Bangka Tengah Police is capable of adjusting to the current requirements, resulting in improved budget use. The Bangka Tengah Police can improve budget absorption by implementing monthly budget realization. No prior research has been conducted on budget absorption at the Police Station during the Covid-19 pandemic, which had a widespread impact on all aspects of life.